Gender-based Violence Against Women and Domestic Violence - Merebashvili, Natia (Journal of Law, 2023)
Violence against women is widespread issue and crime all around the world. Despite that states and international organizations have made great efforts in this direction, the latent nature of this crime and the existing Stereotyped attitudes prevent it from being effectively combated, especially if there is gender-based violence, which is much more difficult to effectively respond to and prevent than a one-time, violence as situational action. Gender-based violence is more prevalent in cases of domestic violence and this makes it even more difficult to detect the crime, its correct classification and fight against it. The article reviews the compatibility of Georgian National Legislation with International Documents regulating this issue, the nature of gender-based violence, the issue of defining motive in criminal cases and Practice of Georgian and European Courts of human rights.